Controlled release of acetylsalicylic acid from polythiophene/carrageenan hydrogel via electrical stimulation. (10th February 2016) - Pairatwachapun, Sanita; Paradee, Nophawan; Sirivat, Anuvat
Highlights: Fabrication of transdermal patch using PTh/carrageenan blend hydrogel. Drug was released by Fickian diffusion mechanism. Diffusion coefficient depended on crosslinking ratio or crosslinking ionic radii. Diffusion coefficients were greater with the applied electrical potentials. Diffusion coefficients with PTh as the drug carrier were higher than without PTh. Abstract: Blends between polythiophene (PTh) and a carrageenan hydrogel were fabricated as the matrix for the electric field assisted drug release. The pristine carrageenan and the blend films were prepared by the solution casting using acetylsalicylic acid (ASA) as the anionic model drug and Mg 2+, Ca 2+, and Ba 2+ as the crosslinking agents. The ASA was released by the Fickian diffusion mechanism. The diffusion coefficient decreased with increasing crosslinking ratio or decreasing crosslinking ionic radii. The diffusion coefficients were greater with the applied electrical potentials by an order of magnitude relative to those without electric field. Moreover, the diffusion coefficients with PTh as the drug carrier were higher than those without PTh. Thus, the presence of the conductive polymer in the hydrogel blend coupled with applied electric field is shown here to drastically enhance the drug delivery rate.